Fleksibilitas Hak Perempuan dalam Cerai Gugat di Pengadilan Agama Parepare - Fikri Fikri (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
This study aimed to know about the flexibility of women's rights in divorce at Parepare Religious Court and how the judge resolved divorce case. This study was conducted with qualitative research with a focus on case studies, with a juridical, socio-anthropological, philosophical and psychological approach. The results of this study shows; 1) Judge's decision in Case No.171/Pdt.G/2019/PA.Pare is flexible in deciding divorce case. The case of divorce is a reflection of equality and justice in women's rights to law enforcement in the Religious Courts. Divorced as well as eliminating patriarchal culture by placing women as second class; 2) The judge at Religious Court in Parepare can approve in a divorce case for several reasons as follows; disputes and quarrels occur between husband and wife, the husband persecutes and hurts his wife's body, the husband betrays his wife to another woman.